ANALISIS PENGARUH PENERAPAN GOOD GOVERNANCE, SISTEM AKUNTANSI PEMERINTAHAN DAN PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN STUDI PADA SELURUH SKPD PENGELOLA KEUANGAN PEMERINTAH KABUPATEN/KOTA SE-JAWA TENGAH - Amiroh Zumar Hanifah; Haryanto Haryanto (Diponegoro Journal of Accounting, 2021)
This study aims to determine the effect of implementing good governance, government accounting systems and internal control on the quality of financial reports. In this study the dependent variable consisting of Good Governance, Government Accounting Systems and Internal Control. The independent variable in this study is the Quality of Financial Statements.This research was conducted with primary data, namely distributing questionnaires to predetermined populations and samples, namely all SKPD Financial Managers in BPPKAD / BPKAD / BPKD / DPPKAD / BKD throughout Central Java. Data analysis techniques used PLS (Partial Least Squares) softwareThe results showed that the implementation of good governance had no significant effect on the quality of financial reports, while the application of the government accounting system and internal control had a significant effect on the quality of financial reports.